Assessment of cytotoxicity and antibacterial effects of silver nanoparticle-doped titanium alloy surfaces. Issue 9 (September 2019) - Kirmanidou, Yvoni; Sidira, Margarita; Bakopoulou, Athina; Tsouknidas, Alexandros; Prymak, Oleg; Papi, Rigini; Choli-Papadopoulou, Theodora; Epple, Matthias; Michailidis, Nikolaos; Koidis, Petros; Michalakis, Konstantinos
Highlights: The AgNP-doped Ti6 Al4 V surfaces preserved high rates of osteoblast cell viability. The AgNP-doped Ti6 Al4 V surfaces preserved high rates of osteoblast cell proliferation. The AgNP-doped Ti6 Al4 V surfaces showed antibacterial effects against P. gingivalis . The AgNP-doped Ti6 Al4 V surfaces showed antibacterial effects against P. intermedia . The AgNP-doped Ti6 Al4 V surfaces could be proposed for dental implant applications. Abstract: Objectives: This study aimed to develop silver nanoparticle (AgNP)-doped Ti6 Al4 V alloy surfaces and investigate their antibacterial properties against representative periopathogens and potential cytotoxicity on osteoblastic cells. Methods: AgNPs of different size distributions (5 and 30 nm) were incorporated onto the Ti6 Al4 V surfaces by electrochemical deposition, using colloid silver dispersions with increasing AgNP concentrations (100, 200 and 300 ppm). The time-course silver release from the specimen surfaces to cell culture media was assessed by Atomic Absorption Spectroscopy (AAS). Cell attachment, viability and proliferation were investigated by SEM, live/dead staining MTT and BrdU assays. The antibacterial effects were assessed against P. gingivalis and P. intermedia by serial dilution spotting assays. Results: A time- and concentration-dependent silver release from the experimental surfaces was observed. Overall, cell viability and attachment on the AgNP-doped surfaces, suggested adequate cytocompatibility at all concentrations. A transient cytotoxic effect was detected at 24 h for the 5 nm-sized groups that fully recovered at later time-points, while no cytotoxicity was observed for the 30 nm-sized groups. A statistically significant, concentration-dependent decrease in cell proliferation rates was induced at 48 h in all AgNP groups, followed by recovery at 72 h in the groups coated with 5 nm-sized AgNPs. A statistically significant, concentration-dependent antibacterial effect up to 30% was confirmed against both periopathogens. Significance: This study sheds light to the optimal size-related concentrations of AgNP-doped Ti6 Al4 V surfaces to achieve antibacterial effects, without subsequent cytotoxicity. These results significantly contribute to the development of antibacterial surfaces for application in oral implantology.